The effect of transcranial direct current stimulation and inhibitory control training on depression and anxiety among post-stroke individuals - Csaba Kazinczi; Noemi Szepfalusi; Viola Luca Nemeth; Adrienn Holczer; Katalin Jakab; Laszlo Vecsei; Peter Klivenyi; Anita Must; Mihaly Racsmany (BMC Neurology)
Abstract Background Recent research has highlighted the role of fronto-parietal brain networks and cognitive control in mood disorders. Transcranial direct current stimulation (tDCS) and computer-based cognitive training are used in post-stroke rehabilitation. This study examined the combined effects ofof computer-based inhibitory control training (ICCT) and anodal tDCS on post-stroke depression and anxiety. Methods Thirty-five participants were randomly assigned to one of three groups: active tDCS treatment (A), sham tDCS treatment with ICCT (T), or active tDCS with ICCT (AT), for a duration of ten days. Primary outcome measures included the Beck Depression Inventory (BDI), Hamilton Depression Rating Scale (HAM-D), and Spielberger’s State-Trait Anxiety Inventory (STAI-S/T). Statistical analysis was performed using a Mixed-model Analysis of Variance, with supplementary Bayesian analysis. Results The AT group showed a significant improvement in BDI scores (p < .001), whereas no significant effects were observed on the HAM-D, STAI-T, or STAI-S scales. Conclusions The combination of tDCS and ICCT reduced depressive symptoms as measured by the BDI; while no significant effects were found with either treatment alone. Further research is needed to explore the mechanisms behind the synergistic effects in the treatment of post-stroke mood disorders.